“Every crazy person has their own mania” program: Promoting mental health and interdisciplinary training in an institution open to children, adolescents, and adults - Uliana Miranda, Geane; Ferreira dos Santos, Camilla; Gomes da Cunha, Juliana; Carvalho Martins, Thamy Cristine; de Oliveira Ribeiro, Raiany; Abreu Dias, Lorena (Guará Journal, 2025)
This program aims to promote mental health; provide interdisciplinary treatment; and foster the involvement and transformation of patients, students, and professionals. This clinic involves developing a therapeutic plan for each patient, comprising individual, group, and family care, as well as therapeutic workshops. The services that comprise CACIA UFES include: reception, referrals, individual and family care, and therapeutic workshops in social communication, storytelling, expression, imagination, methods and techniques for using mosaics, modeling, music, lyrics, and painting. The program serves children, adolescents, and adults from the university community and those in partnership with HINSG/SESA, accommodating all needs.
Keywords: Mental Health; Promotion of health; Psycotherapy